2016
DOI: 10.1177/1096348014538053
|View full text |Cite
|
Sign up to set email alerts
|

Nature-Based Tourism Destinations

Abstract: This article takes a dyadic approach to the conceptualization of nature-based tourism (NBT) destinations. Treating the natural area and its gateway city as distinct evaluative objects, we propose that tourists may differentially assess each element of a city-park dyad based on the degree to which the attributes of each are perceived as conducive to the fulfillment of NBT-specific goals. By empirically testing this perspective, this study reveals the unique complexities of NBT. The findings indicate that nature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 54 publications
0
22
0
Order By: Relevance
“…For example, one study [47] found that visitors tend to be more positive in their perceptions of urban forests when surveyed in a location with diverse and dense urban forests. Another study [7] also reported that tourists assess natural areas and their gateway cities differently with the former being more likely to create a positive image than the latter. Locations with different types of on-site factors (i.e., presentation platform and support services) have also been found to influence visitors' perceptions and satisfaction [48].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…For example, one study [47] found that visitors tend to be more positive in their perceptions of urban forests when surveyed in a location with diverse and dense urban forests. Another study [7] also reported that tourists assess natural areas and their gateway cities differently with the former being more likely to create a positive image than the latter. Locations with different types of on-site factors (i.e., presentation platform and support services) have also been found to influence visitors' perceptions and satisfaction [48].…”
Section: Discussionmentioning
confidence: 98%
“…Surveys were mostly conducted on Fridays, Saturdays, and Sundays from 9:00 to 17:00. The three-day survey period has also been used by other researchers [7].…”
Section: Samplementioning
confidence: 99%
See 1 more Smart Citation
“…Whilst wellness tourism and cultural tourism are distinct, there are significant overlaps; in both cases the quality of the experience and the environment in which it takes place is paramount. Jafari (1982) states that the natural characteristics and environment of a destination can often be utilised to create and maintain a distinctive destination image for potential visitors (Beerli and Martin, 2004;Line and Costen, 2014). Furthermore, for many destinations (including Forks) it is these types of natural attributes and environments that may be considered as their main resources as well as being key selling points for tourists (Yoon et al, 2015).…”
Section: Attraction Diversificationmentioning
confidence: 99%
“…Second, Su et al (2018) show that previous analyses mainly focused on the green and social practices of individual firms, whereas analyses regarding the green and social responsibility of entire tourist destinations are quite limited. Concentrating only on single-level factors does not recognize the qualitative differences among attributes that constitute the macro or micro environment, which would reduce the explanatory power of empirical analysis (Line and Costen, 2017). Consequently, this study was designed to provide empirical evidence of the relationship between green pull motives and tourist satisfaction by building a multilevel analysis in an attempt to provide a more comprehensive understanding of the processes by which tourist satisfaction is derived.…”
Section: Introductionmentioning
confidence: 99%